Detection of the MYD88 p.L265P Mutation in the CSF of a Patient With Secondary Central Nervous System Lymphoma - Zorofchian, Soheil; Lu, Guangrong; Zhu, Jay-Jiguang; Duose, Dzifa Y.; Windham, Justin; Esquenazi, Yoshua; Ballester, Leomar Y. (Frontiers in Oncology, 2018)
Primary Central Nervous System Lymphoma (PCNSL) and Metastatic (or Secondary) Central Nervous System Lymphoma (MCNSL) are rare central nervous system (CNS) malignancies that exhibit aggressive clinical behavior and have a poor prognosis. The majority of CNS lymphomas are histologically classified as diffuse large-B cell lymphoma (DLBCL). DLBCL harbors a high frequency of mutations in MYD88 and CD79b. The MYD88 p.L265P mutation occurs at high frequency in CNS lymphoma and is extremely rare in non-hematologic malignancies. Currently, brain biopsy is considered the gold standard for CNS lymphoma diagnosis. However, brain biopsy is invasive, carries a risk of complications, and can delay initiation of systemic therapy. Circulating tumor DNA (ctDNA) in the cerebrospinal fluid (CSF) can be utilized to detect tumor-derived mutations. Testing of CSF-ctDNA is a minimally-invasive methodology that can be used to assess the genomic alterations present in CNS malignancies. We present a case of an 82-year-old man with a history of testicular lymphoma who presented with speech difficulty and a multifocal enhancing left inferior frontal mass. Analysis for both CSF-cytology and flow cytometry did not show evidence of neoplastic cells. A brain biopsy was performed and microscopic examination showed DLBCL. We isolated CSF ctDNA and used droplet digital PCR (ddPCR) to detect the most common lymphoma-associated mutations in MYD88, L265P, and V217F. In conjunction, we evaluated the patient-matched CNS lymphoma tissue for MYD88 mutations. We detected the MYD88 p.L265P mutation in formalin fixed paraffin embedded (FFPE) tissue from the brain biopsy and the CSF ctDNA. In contrast, both the tumor tissue and the CSF ctDNA were negative for the MYD88 p.V217F mutation. This study shows that testing CSF ctDNA for MYD88 mutations is a potentially minimally-invasive approach to diagnosing patients with suspected CNS lymphomas.